Malay Rebab: Sound Analysis of the Kelantan Traditional Musical Instrument - Aaliyawani Ezzerin, Sinin; Sinin, Hamdan; Khairul Anwar, Mohamad Said; Marini, Sawawi; Khairil Anwar Dean, Kamarudin; Ahmad Faudzi, Musib (North Carolina State University, 2025)
The ‘Malay’ rebab is a vertical, strung chordophone played similarly to a cello. The rebab strings sit on a bridge. The bridge is placed on a buffalo intestine on the front face. The buffalo intestine surface is pressed by the bridge in such a way that the string tension is not in a fully stable position. A ball of beeswax attached near the bridge mutes the sound reverberations. This investigation was undertaken by analyzing the rebab sound utilizing Fast Fourier Transform (FFT) for spectrum analysis via a PicoScope. The highest note is Bb (Bb3 = 0.231 kHz), played on the 1st string. The intermediate note is F (F3 = 0.172 kHz) played on the 2nd string. The lowest note is C (C3 = 0.135 kHz), played on the 3rd string. For string 1, the fundamental pitches (f0) were 0.222 kHz, 0.237 kHz and 0.224 kHz for rebab A, B, and C, respectively. For string 2, the f0 were 0.174 kHz, 0.177 kHz and 0.168 kHz for rebab A, B and C respectively. For string 3, the f0 were 0.125 kHz, 0.149 kHz and 0.126 kHz for rebab A, B and C respectively. All the strings show non-harmonicity.